Analysis of food allergy in atopic dermatitis patients - association with concomitant allergic diseases - Jarmila Celakovská; Josef Bukac (Wolters Kluwer Medknow Publications, 2014)
Background: A few reports demonstrate the comorbidity of food allergy and allergic march in adult patients. Aims and Objectives: To evaluate, if there is some relation in atopic dermatitis patients at the age 14 years and older who suffer from food allergy to common food allergens to other allergic diseases and parameters as bronchial asthma, allergic rhinitis, duration of atopic dermatitis, family history and onset of atopic dermatitis. Materials and Methods: Complete dermatological and allergological examination was performed; these parameters were examined: food allergy (to wheat flour, cow milk, egg, peanuts and soy), the occurrence of bronchial asthma, allergic rhinitis, duration of atopic dermatitis, family history and onset of atopic dermatitis. The statistical evaluation of the relations among individual parameters monitored was performed. Results: Food allergy was altogether confirmed in 65 patients (29%) and these patients suffer significantly more often from bronchial asthma and allergic rhinitis. Persistent atopic dermatitis lesions and positive data in family history about atopy are recorded significantly more often in patients with confirmed food allergy to examined foods as well. On the other hand, the onset of atopic dermatitis under 5 year of age is not recorded significantly more often in patients suffering from allergy to examined foods. Conclusion: Atopic dermatitis patients suffering from food allergy suffer significantly more often from allergic rhinitis, bronchial asthma, persistent eczematous lesions and have positive data about atopy in their family history.